Fundamentals of nursing models, theories and practice - McKenna, Hugh P.; Pankhihar, Majda; Murphy, Fiona
"A concise, accessible introduction to the development, application and evaluation of nursing theories, this new edition of Fundamentals of Nursing Models, Theories & Practice provides a thorough overview of the body of knowledge on the topic, and a clear outline of their relevance to everyday nursing practice. Linking the development of theory to practice, this full-updated text features learning outcomes, key concept summaries and reflective exercises to aid the study of this key element of all modern nursing courses. Special Features- Clearly examines the relationship between nursing theory, clinical practice and nursing roles- Accessible and user-friendly with a range of features to help study, including key concepts, learning objectives and reflective exercises- Useful for all pre-registration nursing students, as well as newly qualified nurses- Accompanied by an online resource centre featuring case studies, multiple choice questions, exercises and activities"--Provided by publisher.
Machine generated contents note: Dedication Preface Chapter 1 The case for nursing theory Chapter 2 Knowing in nursing and nursing knowledge Chapter 3 Theory from practice and practice from theory Chapter 4 Nursing theories and new nursing roles Chapter 5 Nursing theories or nursing models Chapter 6 Interpersonal relationships: the essence of nursing models and theories Chapter 7 How to select a suitable model or theory Chapter 8 Research and theory: some relationships Chapter 9 Criteria for theory description, analysis and evaluation References Index.
Keywords: Nursing Theory; Models, Nursing; Nursing Process